Identification of Volatile Components of Flowers Of Zephyranthes Candida (Lindl.) Herb. (Bangladesh Journal of Botany, 2022)
The volatile components of Zephyranthes candida flowers were extracted using headspace-solid phase micro-extraction (HS-SPME) technique and then were analyzed by gas chromatography-mass spectrometry (GC-MS) for the first time. The major compounds of volatile extract were found to be 1-hexanol (15.4%), methyl heptanoate (12.8%), hexyl acetate (4.9%), 2-acetyl pyrrole (3.6%), methyl-α-D-rhamnopyranoside (3.0%), phenethyl alcohol (2.8%), heptanoic acid (2.7%), and 1-octanol (2.1%).Bangladesh J. Bot. 51(1): 175-178, 2022 (March)